2018
DOI: 10.1186/s12875-018-0775-9
|View full text |Cite
|
Sign up to set email alerts
|

Risk of opioid misuse in chronic non-cancer pain in primary care patients - a cross sectional study

Abstract: BackgroundEfforts to improve treatment of pain using opioids have to adequately take into account their therapeutic shortcomings which involve addictiveness. While there are no signs of an “opioid epidemic” in Germany similar to that in the US, there is little data on the prevalence of prescription opioid misuse and addiction. Therefore, our objective was to screen primary care patients on long-term opioid therapy for signs of misuse of prescription opioids.MethodsWe recruited 15 GPs practices and asked all pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
0
13
0
3
Order By: Relevance
“…Still, there is little data with a focus on diagnosing addiction or misuse in patients receiving prescription opioids. Two recent, cross-sectional trials in Germany showed that a significant proportion of ambulatory patients with CNCP and long-term opioid therapy (LTOT) were at high risk of opioid misuse (31.5%) or had been diagnosed with prescription opioid use disorder (pOUD) (26.5%), yet both trials lacked in size and generalizability [10,11]. Additional analysis from larger datasets would be useful to assess the situation in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…Still, there is little data with a focus on diagnosing addiction or misuse in patients receiving prescription opioids. Two recent, cross-sectional trials in Germany showed that a significant proportion of ambulatory patients with CNCP and long-term opioid therapy (LTOT) were at high risk of opioid misuse (31.5%) or had been diagnosed with prescription opioid use disorder (pOUD) (26.5%), yet both trials lacked in size and generalizability [10,11]. Additional analysis from larger datasets would be useful to assess the situation in Germany.…”
Section: Introductionmentioning
confidence: 99%
“…This result is important because, while Europe does not face an "opioid epidemic," addiction to opioids should be considered when using them in CNCP and should therefore be closely monitored. 6 The OPRM1 gene could therefore help us to evaluate the most frequent opioid AEs: gastrointestinal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…The patients reported a total of 1659 AEs in a total of 359 visits (median of 7 [4][5][6][7][8][9] EAs/visit). The most frequent AEs classified by system were psychiatric (21%) and gastrointestinal disorders (20%; Figure 3A).…”
Section: Adverse Events and Suspected Adverse Drug Reactions Reportedmentioning
confidence: 99%
See 2 more Smart Citations